Bulletin / International Federation of General Factory Workers. . Bulletin / International Federation of Industrial Organisations and General Workers' Unions
Since (1950):no.3: International Federation of Industrial Organisations and General Workers' Unions. - (1964):no.2-3 titled: IFF bulletin. - Since (1964):no.4 titled: ICF bulletin. International Federation of Chemical and General Workers' Unions.